Structural responses of a conceptual microsatellite structure incorporating perforation patterns to dynamic launch loads - Salman Dawood, Sarmad Dawood; Harmin, Mohammad Yazdi (Multidisciplinary Digital Publishing Institute, 2022)
Satellite systems undergo several operational phases during their service life, including the assembly phase, ground transportation phase, the launch phase, and the in-orbit operation phase. Among these phases, the one that imposes the highest level of loadings on the satellite is the launch phase. This phase involves a number of highly dynamic loads, all being imposed upon the satellite simultaneously. Investigation of the responses of the structural subsystem of a satellite to these loadings, namely its maximum deformations and maximum von Mises stresses, is critical if a reasonably high level of confidence is to be achieved. This confidence is in terms of ensuring that no material yielding develops in the structure as a result of the imposed launch loadings. In an earlier work, the structural subsystem of a conceptual microsatellite was designed, employing aluminum 6061 alloy as its material. It was then modified through introducing sets of parametrically defined geometric patterns as perforation patterns to remove material, towards reducing the structure’s total mass, as an alternative to employing composite materials. That effort led to a mass reduction percentage of 23.15%. The current work’s research effort focused on computing the responses of the perforated structure to three of the dynamic launch loads that are imposed upon satellites while being launched, namely quasi-static, random, and shock loads. These responses were then compared to those of the baseline, unperforated, version of the same structure. The values of these loads were taken from the relevant sources, with the values being nominal, and represented the loads that any satellite must qualify for before it can be accepted by the provider for inclusion in a launcher. After imposing these load values upon the structural design it was found that the structural responses indicated that the structure would successfully survive these loads without developing stresses that would lead to material yielding failure. This was deduced from computing the yield margins of safety for each loading case, and all margin values were positive, indicating that the structure, at its current development stage, did have sufficient capacity to withstand these loads without material yielding. This reinforced the conclusion of the earlier work, namely that the perforation concept did have sufficient merit to be further developed towards being implemented in future satellite designs.